Titian : his life - Hale, Sheila (London : HarperPress, 2012)
The first biography since 1877 of Venice's greatest artist - a towering work which captures the genius of Titian, beautifully illustrated throughout with full colour plates.
Includes bibliographical references (p. 789-802) and index.
boek
Keywords: Titian, -- ca. 1488-1576.; Painters -- Italy -- Venice -- Biography